Quantifying sedimentary ’blue carbon’ in relation to canopy cover in the seagrass meadows of Turneffe Atoll, Belize - Felgate, Stacey L.; Sanders, Richard; Andrade, Valdemar; Barry, Christopher D. G.; Brittain, Hannah; Carpenter, Stephen; Carrias, Abel; Cobb, Eliceo; Evans, Chris D.; Hunt, James; Lichtschlag, Anna; Mayor, Daniel J.; et al. (Frontiers in Marine Science, 2024)
Seagrass sediments are important 'blue carbon' reservoirs which store climatically significant quantities of organic carbon (Corg) at the global scale. Seagrass meadows that overly these sediments also provide a range of critical ecosystem services including shoreline stabilization, storm surge protection, and fisheries nursery grounds. However, the controls over accumulation and the sources of organic C to these sediments beds are highly variable and poorly understood with the relative importance of hydrodynamic setting, species composition and canopy density being unclear. Here we address these questions using the report the first observation-based estimates of Corg stocks and provenance on Turneffe Atoll, Belize, using made via remotely-sensed habitat extent, local Corg data and isotopic data. Sedimentary Corg was highest in sediments underlying the most sheltered meadows and decreased with increasing exposure to wind and wave energy with the seagrass meadows in the central lagoon containing an extensive deposit of mangrove derived organic carbon, stabilized and protected by the overlying seagrass meadow. The influence of species composition appeared weak with the ubiquitous species T. testudinum occurring across a wide range of hydrodynamic regimes ranging from the most sheltered to the most energetic and being associated with a wide range of sedimentary organic C concentrations. and were not influenced by seagrass canopy cover. Importantly from the perspective of remote sensing, org C concentrations were unrelated to canopy density. We hypothesise that this decoupling of organic C concentration from seagrass canopy cover reflects a much longer timescale for carbon storage in the sediments than the lifespan of the seagrass plants themselves and /